2016
DOI: 10.1017/s0014479716000065
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Lateral Root Growth and Leaf Quality of Flue-Cured Tobacco by the Combined Application of Humic Acids and NPK Chemical Fertilizers

Abstract: SUMMARYIn this study, the effects of HA combined with NPK fertilizer (HANPK) on root growth and leaf quality of tobacco plants were investigated in tobacco fields. Results indicated that the application of HA alone did not enhance the growth of tobacco obviously, while HANPK increased tobacco biomass by 36.9% and stimulated the growth of lateral roots significantly. The number of the second-order lateral roots was increased by 89.3% compared with the control. Furthermore, HANPK raised the ratio of root biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…However, no significant correlation between tobacco sugar and elevation ( p > 0.05) might be due to the complex and changeable soil properties across all the samples (Table S1 ). In this study, the low potassium level in almost all samples corresponds to a previous research that tobacco potassium content is typically lower than 2% in China 30 , results in restricting the improvement of tobacco quality 6 . The results of our study showed correlations between the tobacco potassium and soil AvK, nitrate, AvP, as well as elevation (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, no significant correlation between tobacco sugar and elevation ( p > 0.05) might be due to the complex and changeable soil properties across all the samples (Table S1 ). In this study, the low potassium level in almost all samples corresponds to a previous research that tobacco potassium content is typically lower than 2% in China 30 , results in restricting the improvement of tobacco quality 6 . The results of our study showed correlations between the tobacco potassium and soil AvK, nitrate, AvP, as well as elevation (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It is of utmost attention that increasing the potassium levels in tobacco leaves is a vital but difficult work in tobacco planting in China 6 , 43 . Despite that the tobacco potassium had no relationship with soil fungal communities at the species level, its positive association with soil Trichoderma genus (r = 0.525, p < 0.05) would make it possible in improving the potassium content by biotechnology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AUX-like effect is the most well-known phytohormonal behavior of HS and has been examined in the literature for over half a century [41]. Root elongation and lateral root emergence are recognized, as morphological impacts of HA [42,43]. This effect has been associated with the activation of the plasma membrane (PM) enzyme H + -ATPase by small molecules present in HA endowed with auxinic activity [42].…”
Section: Auxin (Aux)mentioning
confidence: 99%
“…Cai et al (2013) found that a combination of compost and chemical fertilizer (1:1) could improve the nitrogen use efficiency and reduce N 2 O emissions from the soil during corn-wheat rotation. Shen et al (2017) combined applications of humic acid and NPK fertilizer and found that these fertilizers increased the biomass of flue-cured tobacco by 36.9%, increased the root biomass of the soil layer by 0 to 20 cm, and increased the yield by 12.2%. Zhang et al (2016) found that replacing 30% nitrogen fertilizer with compost (cow manure) increased nitrogen absorption, yield, and soil invertase activity, reduced nitrogen loss, and improved soil quality after 3 years of experiments.…”
mentioning
confidence: 99%